In-situ spectroelectrochemical study of highly active Ni-based foam electrocatalysts for hydrogen evolution reaction - Bazán Aguilar, Antony Yamir (2023)
Green hydrogen is a valuable energy source able to overcome the environmental issues generated by fossil fuel consumption. In this regard, large-scale production of green hydrogen could be achieved by anion exchange membrane water electrolyzer (AEMWE). However, highly electroactive, and low-cost catalysts for hydrogen evolution reaction (HER) are critical to executing AEMWE. With this end in view, a straightforward route is revealed to improve the catalytic performance toward the HER of commercial and low-cost Ni foam electrodes. Indeed, an oxyhydroxide nickel-based surface was obtained after a facile and low-cost anhydrous etching procedure of the raw material. The novel catalyst reveals an onset potential for the HER of ca. 10.0 mV (vs. RHE), which is very close to the thermodynamic value, and an increment of the catalytic efficiency towards the HER. Furthermore, differential electrochemical mass spectrometry (DEMS) and Raman spectroelectrochemistry (Raman-SEC) were employed to get insight into the reaction kinetics and mechanism of the HER at catalysts in alkaline medium.